Knowledge, attitude and practice of condom use by women of an impoverished urban area - Smalyanna Sgren da Costa Andrade; Ana Aline Lacet Zaccara; Kamila Nethielly Souza Leite; Karen Krystine Gonçalves de Brito; Maria Júlia Guimarães Oliveira Soares; Marta Miriam Lopes Costa; Ana Karina Bezerra Pinheiro; Simone Helena dos Santos Oliveira (SciELO, 2015)
OBJECTIVE Assessing the adequacy of knowledge, attitude and practice of women regarding male and female condoms as STI/HIV preventive measures. METHOD An evaluative Knowledge, Attitude and Practice (KAP) household survey with a quantitative approach, involving 300 women. Data collection took place between June and August 2013, in an informal urban settlement within the municipality of João Pessoa, Paraiba, Northeast Brazil. RESULTS Regarding the male condom, most women showed inadequate knowledge and practice, and an adequate attitude. Regarding the female condom, knowledge, attitude and practice variables were unsatisfactory. Significant associations between knowledge/religious orientation and attitude/education regarding the male condom were observed. CONCLUSION A multidisciplinary team should be committed to the development of educational practices as care promotion tools in order to improve adherence of condom use.